Pelanggaran Desersi Pada Prajurit Militer - Astri Dewi Setyarini; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In this discussion, the author refers to what desertion is, and how to regulate and resolve desertions committed by military members. The author uses a normative juridical research method where the researcher uses studies from legal sources such as laws, journal papers and books. Desertion is an act of a military member leaving his duties and responsibilities without official permission or a valid reason. This desertion is resolved through the Military Court and carries out a whole series of trials until finally the member is proven guilty of committing the crime of desertion or not.